(untitled) - Ondrus, Jan; Dicova, Jana (Doprava a spoje, 2011)
The road charging in urban areas is very simple and efficient way to reduce traffic volumes, lower congestions or to limit individual transportation demand in the centres. In our paper we would like to focus on some steps of the introduction of road charging, and those are the basic design elements of the system. Here it is necessary to point out that the toll is not only a technological issue but also the economic, public, especially political and legislative and politicians will decide on individual items, including the introduction of such a system